Influence of physical factors on activation of Saccharomyces cerevisiae yeast p. 11 - Bilyaev, Igor; Romanova, Zoriana; Kosoholova, Liudmyla (Problems of Environmental Biotechnology, 2024)
The influence of physical factors on the activation of Saccharomyces cerevisiae yeast p. 11